The purpose economy : expanded and updated - Hurst, Aaron, ....- (Boise : Elevate, 2016)
In 2014 Aaron Hurst, Ashoka fellow and founder of Imperative and Taproot Foundation, published The Purpose Economy, the book that catalyzed the purpose revolution. With his prediction that purpose was the next major economic era, many are now racing to find answers and direction toward discovering their personal, professional, and organizational purpose. Leaders from around the world have embraced Hurst s work and have asked for more. In this expanded and updated edition Hurst unpacks critical new research and tools for individuals and organizations to find purpose and thrive in this new era. Based on interviews with hundreds of entrepreneurs, a new survey of over 100,000 people and refined societal trends, Hurst shows that this new era is fueling demand for purpose-centered professionals who not only create more satisfying careers, but also contribute more productively to teams and organizations. A new view of success based on relationships, impact, and growth is spreading across the globe, and individuals and organizations that embrace that view have emerged as the leaders of the new economy.
Keywords: Etisch ondernemen